Reduced Orthodontic Tooth Movement in Enpp1 Mutant Mice with Hypercementosis. (July 2018) - Wolf, M.; Ao, M.; Chavez, M.B.; Kolli, T.N.; Thumbigere-Math, V.; Becker, K.; Chu, E.Y.; Jäger, A.; Somerman, M.J.; Foster, B.L.
Previous studies revealed that cementum formation is tightly regulated by inorganic pyrophosphate (PPi ), a mineralization inhibitor. Local PPi concentrations are determined by regulators, including ectonucleotide pyrophosphatase/phosphodiesterase 1 (ENPP1), which increases PPi concentrations by adenosine triphosphate hydrolysis. Orthodontic forces stimulate alveolar bone remodelling, leading to orthodontic tooth movement (OTM). To better understand how disturbed mineral metabolism and the resulting altered periodontal structures affect OTM, we employed Enpp1 mutant mice that feature reduced PPi and increased cervical cementum in a model of OTM induced by a stretched closed-coil spring ligated between the maxillary left first molar and maxillary incisors. We analyzed tooth movement, osteoclast/odontoclast response, and tooth root resorption by micro–computed tomography, histology, histomorphometry, and immunohistochemistry. Preoperatively, we noted an altered periodontium in Enpp1 mutant mice, with significantly increased periodontal ligament (PDL) volume and thickness, as well as increased PDL-bone/tooth root surface area, compared to wild-type (WT) controls. After 11 d of orthodontic treatment, Enpp1 mutant mice displayed 38% reduced tooth movement versus WT mice. Molar roots in Enpp1 mutant mice exhibited less change in PDL width in compression and tension zones compared to WT mice. Root resorption was noted in both groups with no difference in average depths, but resorption lacunae in Enpp1 mutant mice were almost entirely limited to cementum, with 150% increased cementum resorption and 92% decreased dentin resorption. Osteoclast/odontoclast cells were reduced by 64% in Enpp1 mutant mice, with a predominance of tartrate-resistant acid phosphatase (TRAP)–positive cells on root surfaces, compared to WT mice. Increased numbers of TRAP-positive cells on root surfaces were associated with robust immunolocalization of osteopontin (OPN) and receptor-activator of NF-κB ligand (RANKL). Collectively, reduced response to orthodontic forces, decreased tooth movement, and altered osteoclast/odontoclast distribution suggests Enpp1 loss of function has direct effects on clastic function/recruitment and/or indirect effects on periodontal remodeling via altered periodontal structure or tissue mineralization.